Analysis Theory of the Law of Convergence in Regulation Licensing and Supervision Financial technology ( Fintech ) in Indonesia - Suyikno; Thohir Luth; Sihabudin; Siti Hamidah (Britain International for Academic Research (BIAR-Publisher), 2022)
The convergence paradigm of the legal order is carried out by examining the approaches to the conception of convergence and the conception of non-convergence in law. The approach is used to find the relationship between similarities and differences in legal systems, or to compare different legal systems to explain the importance of the concept of legal convergence. A legal system will find different ways to approach a similar problem and in practice often achieve functionally similar results. On the other hand, some year lately this, we currently faced with development industry financial technology (fintech) who experienced growth very significant. This thing This is evidenced by the increasing number of providers registering and having licenses with relevant regulators, the increasing number and volume of transactions in the community, and the increasing variety of types of digital financial services offered by fintech operators. Development fintech requires the readiness of the Government as a regulator in preparing regulations, especially those related to institutional aspects, business activities, and risk mitigation. In order to maintain the growth of the fintech industry and improve its quality and competitiveness (especially at the regional level), it is necessary to have adequate digital infrastructure, a conducive regulatory climate, the number of human resources with appropriate skills and better digital financial literacy for the community high. Financial Services Authority Republic of Indonesia (OJK -RI), Bank Indonesia (BI) as the central bank as well as Relevant ministries are still preparing and compiling provisions to regulate fintech in Indonesia. To date, a number of technical regulations have been issued by several regulators in relation to the licensing, regulation and supervision of fintech operators.